ANALISIS YURIDIS PENYELESAIAN SENGKETA WARIS BERDASARKAN HUKUM ADAT ANGKOLA DI KABUPATEN TAPANULI SELATAN - FRAMITA UTAMI (PREMISE LAW JURNAL, 2016)
The research problems were how the implementation of inheritance distribution customarily in Angkola community in Tapanuli Selatan Regency, how about the role of adat council if there was a dispute in distributing inheritance in Angkola community, Tapanuli Selatan Regency, and how about legal force of dispute settlement in inheritance according to the Adat Arbitration Council in Angkola community in Tapanuli Selatan RegencyThe implementation of inheritance law in Angkola community, Tapanuli Selatan Regency originally used inheritance law by adat which states only a boy who has the right on inheritance from his parents while a girl does not. She is usually get the property as a gift (Holong Ate), the giving of moveable and immoveable property. However, after the coming of Islam to South Tapanuli the inheritance law changed, especially in those who became Moslems. The Angkola Moslems are subject to the Islamic Inheritance Law: 2 portion for a boy and 1 portion for a girl. Keywords: Settling Dispute in Inheritance, based on Angkola Adat Law in Tapanuli Selatan Regency